parasitic Protozoans infecting free – living fishes of Lake of 16 Tishreen Dam , Lattakia, Syria - Salman, H. M.; Dayoub, A I. (Iraqi Journal of Aquaculture, 2022)
The study included 144 fishes in Lake of 16 Tishreen Dam for detecting the infection with parasitic Protozoans, and determine the distribution rate. Fishes were collected randomly once a month, during the period from 22/12/2011 until 22/12/2012. Collected fishes samples were belonged to the following species: Cyprinus carpio L., Varicorhinus damascinus, Garra rufa, Tilapia zillii, and Liza abu. T. zillii was the most prevalent in the lake of 16 Tishreen Dam. The study has shown presence of three species of parasitic Protozoans on the Skin, Fins and Gills continuously. Trichodina sp. was the most distributed one with a rate of (34.03%) then Ichthyophthirius multifiliis (15.97 %) then Chilodonella cyprini ( 2.78 %). The infection rate of T. zillii with parasitic Protozoans was the highest 54.46 %, Trichodina sp. was 42.57 % ( in Summer 62.26 %), and C. cyprini 3.96 %,( in Summer 7.55 %) whereby the infection rate with I. multifiliis was 19.80 %( in Autumn 33.33 %).